A guide to maximising ball mill circuit classification system efficiency (CSE), for operators and equipment designers - K M. Bartholomew; R E. McIvor; O Arafat (The Australasian Institute of Mining and Metallurgy, 2018)
It is well known in the industry that good classification system performance is vital to efficient ball mill circuit performance. But what is meant by good classification system performance, and how is it achieved? Unfortunately, the perceived complexity of classification systems, and the day-to-day time demands placed on the practicing metallurgist, all too often put the low-hanging fruit of classification system optimisation in the ‘I’ll do it later’ basket. Additionally, lingering confusion about basics such as the relationship between circulating load ratio and ball mill circuit performance makes the optimisation objective seem nebulous to both plant metallurgist and designer.Some of this confusion can be eliminated by taking a step back from the overwhelming detail of sharpness of separation curves, circulating load ratios, cyclone feed pressures, vortex and apex sizes etc, and focusing on the purpose or function of the classification system – to apply mill power to particles that need further size reduction! The classification system efficiency (CSE) metric captures how well the classification system is performing its function with two quick and easy size distribution analyses.Once CSE is understood and implemented as the optimisation criteria, well-tested methods for improving CSE can be implemented and quickly measured at plant scale to give confidence that the right change was made.This paper will describe CSE and how it is measured in practice. Next, a guide for improving CSE through manipulation of design and operating variables in the classification system will be provided. Examples and case studies will illustrate the gains in ball mill circuit efficiency that can be achieved by maximising CSE.CITATION:Bartholomew, K M, McIvor, R E and Arafat, O, 2018. A guide to maximising ball mill circuit classification system efficiency (CSE), for operators and equipment designers, in Proceedings 14th AusIMM Mill Operators' Conference 2018, pp 553–558 (The Australasian Institute of Mining and Metallurgy: Melbourne).